2017
DOI: 10.17576/jkmjc-2017-3301-12
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Batik Lukis Motifs as a Medium of Art Communication in Pahang

Abstract: Malaysian societies are more familiar with batik which hails from Kelantan and Terengganu. They know very little about batik from Pahang which is often more revered for its traditional craft product such as 'tenun Pahang' (woven fabric). In other words, Malaysians are oblivious to the uniqueness of batik lukis from Pahang since much information about it offers only a general description. Based on this understanding, the present qualitative research is carried out through a case study method to explore and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These motifs have their own particular meaning, a certain symbol, message, or hope to be delivered from the pattern of Sasirangan. Research by Ramli et al (2017) showed the motif of a traditional representing images or symbols of plants and the surrounding environment. Traditional fabrics also have various aesthetic values and the meaning of each pattern created (Vivithkeyoonvong et al, 2021;Akhir et al, 2017).…”
Section: Table 2 Sasirangan Motifsmentioning
confidence: 99%
See 2 more Smart Citations
“…These motifs have their own particular meaning, a certain symbol, message, or hope to be delivered from the pattern of Sasirangan. Research by Ramli et al (2017) showed the motif of a traditional representing images or symbols of plants and the surrounding environment. Traditional fabrics also have various aesthetic values and the meaning of each pattern created (Vivithkeyoonvong et al, 2021;Akhir et al, 2017).…”
Section: Table 2 Sasirangan Motifsmentioning
confidence: 99%
“…The distribution system contains the order of ways that must be taken to distribute goods and services to consumers. For the distribution process to run smoothly, distributors must pay attention to various conditions from the producer and consumer sides (Abbas et al, 2019;Abbas & Rajiani, 2017;Bačík et al, 2019;Ramli et al, 2017).…”
Section: Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…This means the motif of the woodcarving is similar to the traditional motif of block batik. In addition, the inspiration for motif batik making usually associates with nature where they attempt to immortalize God"s beautiful creation in their masterpieces [13]. Thus, the reason most of the researchers focus on the main motif, flora, fauna, and geometry [14].…”
Section: Literature Reviewmentioning
confidence: 99%